Wacana Eldest Daughter Syndrome dalam Tagar #anakperempuanpertama di TikTok - Fandi, Fika Amalia Putri Eko; Zuhri, Saifudin (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
This study aims to analyze the discourse of eldest daughter syndrome in TikTok contents using the hashtag #anakperempuanpertama. Employing Rodney H. Jones’s digital discourse analysis method, the research explores four key elements: text, context, action and interaction, ideology and power. The findings reveal that the content predominantly represents emotional burden, loneliness, and gendered responsibilities experienced by firstborn daughters. The narratives are highly personal and affective, amplified by digital interactions such as likes, comments, saves, and shares. TikTok’s algorithm plays an active role in promoting emotionally charged content, contributing to the wider circulation of the discourse. Consequently, the hashtag #anakperempuanpertama serves as a digital space form women to negotiate their identity and voice their lived experiences within patriarchal cultural in Indonesia.
Keywords: Digital Discourse Analysis; Eldest Daughter; Gender; Eldest Daughter Syndrome; TikTok